Employment in Europe 1998. (Employment and social affairs, 1998)
Summary: The Employment in Europe Report 1998 (drawn up on the basis of the document COM(98) 666) presents the latest trends in employment and the labour market and provides the analytical background to the review of the employment strategy and the adoption of the Employment Guidelines for 1999. The full impact of the employment strategy and broader measures promoting an employment-friedly environment will only be felt in the medium and longer-term. The employment strategy is a multi-annual process and sustainable progress will require a continuing commitment over a number of years by the Member States.